Bisphenol A Modifies the Regulation Exerted by Testosterone on 5α-Reductase Isozymes in Ventral Prostate of Adult Rats. (25th July 2013) - Sánchez, Pilar; Castro, Beatriz; Torres, Jesús M.; Olmo, Asunción; del Moral, Raimundo G.; Ortega, Esperanza
Abstract : The development, growth, and function of the prostate gland depend on androgen stimulation. The primary androgen in prostate is 5α -dihydrotestosterone (DHT) which is synthesized from circulating testosterone (T) through the action of 5α -reductase (5α -R). Although 5α -R occurs as five isozymes, only 5α -R1 and 5α -R2 are physiologically involved in steroidogenesis. The endocrine disruptor bisphenol A (BPA) alters sexual organs, including the prostate. Our previous findings indicated that BPA decreased the expression of 5α -R1 and 5α -R2 in rat prostate but also circulating T. Thus, it is unclear whether BPA exerts this effect on 5α -R isozymes by reducing circulating T or by any other mechanism. In this study, we examine the effects of short-term exposure to BPA at doses below 25 μ g/Kg/d and above 300 μ g/Kg/d of the TDI on mRNA levels of 5α -R1 and 5α -R2 in prostate of adult castrated rats supplemented with T to achieve constant circulating T levels. mRNA levels were measured by absolute quantitative RT-PCR, T levels by RIA, and DHT levels by ELISA. Our results indicated that in castrated rats treated with T BPA at the two doses studied significantly decreased the mRNA levels of both 5α -R isozymes in a dose-dependent manner without modifications in circulating T.